Application of information technologies in entrepreneurship - Bilotserkivskyi, Oleksandr (The University of Technology in Katowice Press, 2025)
The purpose of the study is to define the essence of the concept of “information technology” and to analyze their types and functions used in entrepreneurial activity management. An author's definition of information technology is proposed as a set of methods, tools, and processes aimed at the purposeful collection, storage, processing, transmission, and use of data. The main types of information technologies such as operational, analytical, managerial, cloud, mobile, and those used for cybersecurity are considered with their characteristics. The key functions of information technologies including business process automation, resource management optimization, support for managerial decision-making, and improvement of communication efficiency are explored. Their essence and role in enterprise management are revealed.
Keywords: information technologies; entrepreneurship; entrepreneurial activity management; functions of information technologies; business; business process